Antibiotic Susceptibility and Resistance Trends in Uropathogenic Bacteria: A Regional Perspective - Ahmed, Toufiq; Monira, Shirajum; Hasan, G M Sadik; Karim, Md. Masudul; Ahmad, Md. Rasel; Hossin, Md. Immam; Islam, Jahidul (Journal of Neonatal Surgery, 2025)
Background: Antimicrobial resistance (AMR) has emerged as a critical global health challenge, particularly in managing urinary tract infections (UTIs), which are among the most prevalent bacterial infections affecting individuals worldwide. Objective: This study aimed to evaluate the patterns of antibiotic susceptibility and resistance in uropathogenic bacteria isolated from clinical samples in Dhaka, Bangladesh, over one year. Methods: A cross-sectional study design was employed from July 2024 to December 2024, with clinical samples systematically collected from outpatient cases. Pathogen identification utilized standard microbiological techniques, including culture on selective media, biochemical testing, and confirmatory methods. Antibiotic susceptibility testing (AST) was performed using the Kirby Bauer disc diffusion method on Mueller–Hinton agar, following CLSI guidelines. Results: The results highlighted significant variability in resistance patterns across bacterial species. Among Escherichia coli isolates, high susceptibility was observed for imipenem (82%), nitrofurantoin (78%), and linezolid (78%), while resistance to penicillin G (35%) and fosfomycin (30%) was notable. For Klebsiella pneumoniae, meropenem (85%) and netilmicin (82%) demonstrated the highest efficacy, whereas nalidixic acid (30%) and amoxicillin (28%) exhibited substantial resistance. Acinetobacter spp. isolates showed remarkable susceptibility to moxifloxacin (85%) and cefuroxime (84%), but levofloxacin resistance (60%) emerged as a critical concern. Statistical analyses revealed significant demographic trends, with middle-aged participants (40–60 years) comprising the majority of the study population. Gender distribution showed a predominance of female participants (64.8%). Clinical symptoms, including fever (38%), urinary urgency (24%), and burning sensation (22%), were most commonly reported among patients. Conclusion: This study provides critical insights into the evolving resistance patterns of uropathogenic bacteria in a regional context.